Effect of environmental temperature and an inoculant on the fermentation of forage sorghum silage - K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1987)
The inoculants, BioPower®, increased the rate and efficiency of ensiling in Acco Paymaster 351 forage sorghum regardless of storage temperature. The untreated, 60 F silage fermentated slower and had higher pH, lower lactic acid, and higher acetic acid values than its 90 F counterpart.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Inoculant; Fermentation; Sorghum silage